Qualidade energética de diferentes biomassas florestais utilizadas no Oeste Paranaense - Corradi, Giordano Marques (2021)
Unlike other regions of the state, where the supply of forest waste is abundant, the West of Paraná depends almost exclusively on energy forests and a few suppliers of sawmill waste, to meet its energy demand. As it is a region based on agribusiness, the areas available for forestry are limited, requiring that biomass in the form of chips reaches its maximum potential at the lowest cost. Thus, it is necessary that there is a specialized quality control, preventing the fall of the energy conversion of the materials. Therefore, this work aimed to determine the Energy Quality Index of the most commercialized forest biomasses in the region: (i) Chips from whole eucalyptus trees; (ii) Pinus sawmill waste; and (iii) Eucalyptus sawmill residues. The moisture content, bulk density and granulometry were determined in samples of each material, which were then correlated to determine the Quality Index. Sawmill residues showed a lower energy quality than the processed chips of whole eucalyptus trees. This is justified by the high humidity of the pine waste (47%) and the low bulk density (229 kg / m³) of the eucalyptus waste. The chips from whole eucalyptus trees have more suitable characteristics (% U = 36.4%; M.E. = 361kg / m³), meeting the market demands regarding thermal energy in a more qualified way.